2015
DOI: 10.1021/jp509285n
|View full text |Cite
|
Sign up to set email alerts
|

Bimolecular Decomposition Pathways for Carboxylic Acids of Relevance to Biofuels

Abstract: The bimolecular thermal reactions of carboxylic acids were studied using quantum mechanical molecular modeling. Previous work1 investigated the unimolecular decomposition of a variety of organic acids, including saturated, α,β-unsaturated, and β,γ-unsaturated acids, and showed that the type and position of the unsaturation resulted in unique branching ratios between dehydration and decarboxylation, [H2O]/[CO2]. In this work, the effect of bimolecular chemistry (water-acid and acid-acid) is considered with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“… 5,6 Here we developed a novel approach to produce renewable mcl -LAO based on the early studies that propylene can be produced from polyhydroxybutyric acid (PHB) as a thermal degradation product, where the hydroxybutyrate units undergo an intramolecular β-elimination to produce crotonic acid, which is then converted into propylene via decarboxylation. 7 A recent research also reported propylene production from cyanobacterial biomass rich in PHB via HTL, 8 consistent with these thermochemical reactions. We hypothesized that mcl -LAO could be produced from medium chain-length polyhydroxyalkanoic acid ( mcl -PHA) via a similar series of reactions.…”
Section: Introductionsupporting
confidence: 60%
“… 5,6 Here we developed a novel approach to produce renewable mcl -LAO based on the early studies that propylene can be produced from polyhydroxybutyric acid (PHB) as a thermal degradation product, where the hydroxybutyrate units undergo an intramolecular β-elimination to produce crotonic acid, which is then converted into propylene via decarboxylation. 7 A recent research also reported propylene production from cyanobacterial biomass rich in PHB via HTL, 8 consistent with these thermochemical reactions. We hypothesized that mcl -LAO could be produced from medium chain-length polyhydroxyalkanoic acid ( mcl -PHA) via a similar series of reactions.…”
Section: Introductionsupporting
confidence: 60%
“…According to previous studies, a carboxylic acid molecule can be catalyzed by the carboxylic acid group of another carboxylic acid molecule. 38 The detailed catalytic reaction path is shown in Figure 5A-C. Reaction path 1 is that the carboxylic acid molecule forms an eight-membered ring transition state configuration with the carboxyl group of another carboxylic acid molecule to form the enone product (P1).…”
Section: Bimolecular Mutual Catalytic Reactionmentioning
confidence: 99%
“…36 Clark et al theoretically calculated the single-molecule and bimolecular pyrolysis pathways of carboxylic acids related to biofuels. 37,38 The results show that the mutual catalytic dehydration between molecules is more dominant than the dehydration reaction of single molecules. Therefore, the pyrolysis process of unsaturated fatty acids can be clearly understood by combining experiments with density functional theory.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other rate constants in the literature are calculated from theory, estimation methods, or similarity arguments 3 . Clark et al 42,43 . calculated barrier heights and rate constants for the unimolecular and bimolecular pathways of many acids including propionic acid.…”
Section: Introductionmentioning
confidence: 99%